Forages from Subabool Based Agroforestry System and its influence on Soil Productivity - Hazra, C.R. (Journal of Soil and Water Conservation, 2022)
An intensified practice of agro forestry is becoming important specially in arid and semi-arid areas to meet multiple needs of human societies. The tree/shrub which forms the upper canopy layer is very important for its proper selection which will suit to specific ecosystem and the need based production. Subabool (Leucaena leucocephala) is one such plant species recognized all over the world including India for its multi purpose utility. Field studies on agroforestry were conducted to determine the influence of tree species on associated underneath crops, productivity of forages from trees’ shrubs and the soil productivity. The studies were carried out both under irrigated and rainfed conditions Olant associations, crops, trees, forage shrubs in hedge norows and as alley cropping were studied Further, grasses and fodders grown in combination , grown under irrigated condition as well as under silvi ’natural system were examend vis-a-vis open grasslands. orubt iyt tge oisuvukuatutues ti ivtaub iotuibs ti syut soecufuc ivhectuves sycg us fertukutt regaretuib abd vyrukt yo in mechanism to increase in total productivity etc. in .specific systems of production are quite a few.